2020
DOI: 10.1111/ppc.12692
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with problematic social media use among a sample of Lebanese adults: The mediating role of emotional intelligence

Abstract: Purpose: To assess the relationship of smoking (cigarettes or waterpipe), alcohol drinking, alexithymia, self-esteem, anxiety, depression, stress, social phobia, emotional intelligence, impulsivity, insomnia, physical health, and loneliness with problematic social media use (PSMU) in a sample of Lebanese citizens.Methods: This cross-sectional study enrolled 466 participants (January-May 2019).Results: Higher anxiety, alcohol use disorder, and social phobia were correlated with elevated PSMU, while older age wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 45 publications
(72 reference statements)
3
12
0
Order By: Relevance
“…This is consistent with previous studies that have found a relationship between the use of SNs for comparisons and anxiety and depression (Hussain & Griffiths, 2018) as well as with dissatisfaction with life (Verduyn et al, 2017). Also, it is consistent with previous studies that have found a relationship between the addictive use of SNs and anxiety and depression (Barbar et al, 2021;Keles et al, 2020;Malaeb et al, n.d.;Seabrook et al, 2016;Youssef et al, 2021) and lower levels of psychological well-being (Arias-de la Torre et al, 2020;Huang, 2017).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is consistent with previous studies that have found a relationship between the use of SNs for comparisons and anxiety and depression (Hussain & Griffiths, 2018) as well as with dissatisfaction with life (Verduyn et al, 2017). Also, it is consistent with previous studies that have found a relationship between the addictive use of SNs and anxiety and depression (Barbar et al, 2021;Keles et al, 2020;Malaeb et al, n.d.;Seabrook et al, 2016;Youssef et al, 2021) and lower levels of psychological well-being (Arias-de la Torre et al, 2020;Huang, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…The most commonly studied psychological problems related to problematic SNs use are anxiety, depression and psychological well-being, with gambling and cyberbullying as other less frequently related issues (Feijóo et al, 2021). Problematic use, understood as a purely addictive problem, has been associated with higher levels of depression and anxiety (Barbar et al, 2021;Keles et al, 2020;Malaeb et al, 2021;Seabrook et al, 2016 ;Youssef et al, 2021), stress (Hussain & Griffiths, 2018) and poorer psychological wellbeing (Marino et al, 2018b). Problematic SN use, when considered a context for negative social comparison, has also been associated with greater levels of depression (Yoon et al, 2019) and anxiety-depressive symptoms (Schmuck et al, 2019), as well as with lower levels of psychological well-being (Arias-de la Torre et al, 2020;Huang, 2017).…”
mentioning
confidence: 99%
“…In such conditions, older employees become less satisfied with work and less efficient in terms of work performance. At first glance, this result may seem contrary to the result that older persons are less associated with problematic social media usage [60]. However, the absence of problematic social media usage does not mean that social media usage in the elderly has no impact (unfavorable) on job satisfaction and work performance.…”
Section: Discussion Of the Moderating Effects Of Age Of Respondentsmentioning
confidence: 74%
“…A Lebanese study done by Obeid et al 45 had showed that high PIU was found in 3.6% of Lebanese adolescents while 40% had occasional and frequent internet users. 45 Previous studies conducted among Lebanese adults have evaluated the association between problematic social media use and loneliness, 46 alexithymia, 47 memory performance, 48 alcohol use disorder 49 and mental health issues (depression and anxiety). 50 No studies have studied the association between PIU and mental health issues among adolescents.…”
Section: Introductionmentioning
confidence: 99%